Multidisciplinary approaches to gliosarcoma: A case report and review of the literature. Issue 8 (23rd August 2022) - Labak, Collin M.; Rabah, Nicholas M.; Kipke, Jasmine P.; Mahajan, Uma V.; Labak, Kyle B.; Ali, S. Ahmed; Fowler, Nicole; Sloan, Andrew E.
Abstract: A 58‐year‐old right‐handed man presented to our tertiary care center with gliosarcoma (GS) infiltration through the dura, skull, and soft tissue. Patient had a previous history of right temporal GS, with four intracranial surgeries prior to presentation. A multidisciplinary approach was used to treat the lesion and perform reconstruction. Abstract : It is important to consider a multidisciplinary approach when treating highly invasive tumors such as GS and to be mindful of mechanisms of spread while planning resection in index surgeries.